IMPLEMENTASI KEBIJAKAN PEMBERIAN INSENTIF LAUK PAUK DI UNIVERSITAS TADULAKO - Indriasari, Margareta Yenni (Katalogis, 2015)
This study aims to identify and study the Policy Implementation Incentives Lauk Pauk at the University Tadulako. The research method is qualitative research, with informants of 9 (nine), informants were selected based on purposive. Collecting data in this study begins with the observation (observation), interviews, and documentation. The results of the study explained that, Policy Implementation Incentives Lauk Pauk at the University Tadulako not going well "because of the four dimensional researched field, there are three dimensions that are not going well, that" (1) The communication has not done well, where socialization policy of the Ministry of Finance No. 110/PMK.05/2010 on Procedures for Granting and Payment of Eating for civil servants have not been socialized to lecturers and university officials Tadulako, as a result of the policy is not well understood by lecturers and officials, especially the dilution mechanism, (2) desposisi aspect has not gone well, because the use of the software manual is an absolute requirement for dilution, but attendance can be engineered true, the University has not yet estimate Tadulako back absent digital fingerprint attendance list. (3) The structure of the bureaucracy is not going well, because the Standard Operating Procesures (SOP) on implementation Tadulako money eating yet, consequently frequent delays in the disbursement.